Genomic insights into hybridization in a localized region of sympatry between pewee sister species (Contopus sordidulus × C. virens) and their chromosomal patterns of differentiation. Issue 1 (December 2016) - Manthey, Joseph; Robbins, Mark
Abstract Background The Great Plains of the United States includes a large number of hybrid and contact zones between bird species. The amount of gene flow between sister species in these zones ranges from very rare hybridization events to widespread and prevalent introgression. Some of these avian systems have been studied extensively, while others have been indeterminate of whether hybridization exists in areas of sympatry. Using genomic-level approaches allows investigation of genomic patterns of hybridization and gene flow between species—or lack thereof. Methods We investigated a narrow zone of sympatry in Nebraska, USA between pewee species (Contopus sordidulus andC. virens ), for which no hybridization has been confirmed. We used thousands of single nucleotide polymorphisms to identify potential hybridization and investigate genomic patterns of differentiation between these two species. Results We found evidence of multiple hybrid individuals in the contact zone. Little genomic variation was fixed between species, but a large proportion had differentiated allele frequencies between species. There was a positive relationship between genetic differentiation and chromosome size. Conclusions We provided the first conclusive evidence of hybridization betweenC. sordidulus andC. virens, in a region where secondary contact likely occurred due to human disturbance and habitat modification. The genomic patterns of differentiation affirm that these species split in the relatively recent past. Finally, the relationship of chromosome size and genetic differentiation may have resulted from differential rates of chromosomal recombination in songbirds and genetic differentiation between species largely due to genetic drift (possibly in concert with selection).